DA'WAH MESSAGES IN THE LOVE HEAVEN FILM - Edi Saputra; Dewi Sarmita (Universitas Dharmawangsa, 2020)
The main problem of this research is how the messages of preaching in Film Syurga Cinta, so the main problem, namely: 1) How the messages preaching in the film Heavenly Love in terms of semiotics (Roland Barthes) ?, 2) How is the influence of the da'wah messages in the Love Heaven Film on an audience?This type of research is classified as mass communication with film concentration The research approach used is a qualitative descriptive approach. The sources of this research are video files, reference searches via online, journals, books, and thesis. Then, data processing and analysis techniques are carried out with several stages, namely: video analysis, data reduction, data presentation, and concluding. The results of this study indicate that the formulation of the first problem is many contained da'wah messages in its name from the aspects of aqidah, sharia, and morals. But of the three aspects, the most dominant was found by the researcher is the moral aspect. Both in terms of morals to Allah SWT, morals to family and community. Then the second is from the aspect of aqidah, where is the scene what many researchers found includes the pillars of faith and the third Islamic aspects.